2019
DOI: 10.3390/coatings9090535
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Morphological Changes in Water-Induced Early-Stage Degradation in Lead Halide Perovskites

Abstract: With tremendous improvements in lead halide perovskite-based optoelectronic devices ranging from photovoltaics to light-emitting diodes, the instability problem stands as the primary challenge in their development. Among all factors, water is considered as one of the major culprits to the degradation of halide perovskite materials. For example, CH3NH3PbI3 (MAPbI3) and CH(NH2)2PbI3 (FAPbI3) decompose into PbI2 in days under ambient conditions. However, the intermediate changes of this degradation process are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…In both cases, following water exposure, there are small drops in the N/Pb 2+ and I/Pb 2+ ratio (Table S3), consistent with a small amount of cation loss (as seen in a small drop in the C–N/Pb 2+ ratio) and formation of PbI 2 , but cation loss is clearly significantly lower than that on annealing in UHV at 150 °C. Previous studies on MAPbI 3 showed that the sample is completely degraded into volatile components after exposure to 9 mbar of water at room temperature. , These results therefore demonstrate that MA-free mixed-cation perovskite samples prepared under ambient conditions are comparatively stable compared to conventional perovskite materials. The comparison with the much more marked degradation observed on heating in UHV suggests that the primary degradation pathway in the MA-free mixed-cation perovskite samples may be associated with the migration of ions.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In both cases, following water exposure, there are small drops in the N/Pb 2+ and I/Pb 2+ ratio (Table S3), consistent with a small amount of cation loss (as seen in a small drop in the C–N/Pb 2+ ratio) and formation of PbI 2 , but cation loss is clearly significantly lower than that on annealing in UHV at 150 °C. Previous studies on MAPbI 3 showed that the sample is completely degraded into volatile components after exposure to 9 mbar of water at room temperature. , These results therefore demonstrate that MA-free mixed-cation perovskite samples prepared under ambient conditions are comparatively stable compared to conventional perovskite materials. The comparison with the much more marked degradation observed on heating in UHV suggests that the primary degradation pathway in the MA-free mixed-cation perovskite samples may be associated with the migration of ions.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies, involving exposing the samples to an ambient atmosphere with varying relative humidity (RH), have been performed. , Since the RH can vary substantially in the environment through changes in temperature and/or water vapor concentration, and the degradation process also involves other gases and the absorption of light, a clear understanding of the degradation mechanism of these halide perovskite materials requires further investigation. , We anticipate that degradation proceeds from the surfaces and grain boundaries, but there have been rather few investigations by surface-sensitive techniques such as X-ray photoelectron spectroscopy (XPS). Yang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While perovskite solar cells retain >95% of their efficiency after 1000 h under continuous solar illumination at 60 °C, [105] LEDs based on perovskite to date last less than 50 h under operation, [106][107][108] far behind state-of-the-art inorganic quantum dot LEDs and organic LEDs (up to a million hours). [109,110] The stability of PeLEDs is mainly compromised by moisture, [111][112][113] temperature, [114,115] photodegradation, [116][117][118] and bias-induced degradation. [119][120][121] Compared to the low electric field across the absorber layer in perovskite solar cells under operation, the high bias applied in PeLEDs based on relatively thinner active layers (≈500 nm in solar cells to ≈30 nm in PeLEDs) causes severe ion migration in the devices, facilitating structural degradation, charge accumulation at interfaces, and corrosion of metal electrodes.…”
Section: Device Stabilitymentioning
confidence: 99%
“…In their brief report, Li et al [12] propose a metal-dielectric metal structure based on a Fabry-Pérot cavity, and the as-prepared narrow-band absorber can be easily fabricated by the mature thin film technology independent of any nanostructure, which makes it an appropriate candidate for photodetectors, sensing, and spectroscopy. Chen et al [13] performed an in situ investigation of the early-stage CH 3 NH 3 PbI 3 (MAPbI 3 ) and CH(NH 2 ) 2 PbI 3 (FAPbI 3 ) degradation under high water vapor pressure. Their experimental results highlight the importance of the compositional and morphological changes in early stage degradation in perovskite materials.…”
mentioning
confidence: 99%